JACIII Distinguished Editor & Outstanding Reviewer Awards 2023 - Office, Editorial (Journal of advanced computational intelligence and intelligent informatics, 2023)
The JACIII Distinguished Editor and Outstanding Reviewer Awards were established for the purpose to honor editors who have made a significant contribution to the growth of the JACIII in 2018 and to acknowledge reviewers who have made a significant contribution to reviewing in 2022. We express our deepest gratitude for their professional work, which we believe conductive to development of not only the JACIII but also scientific research.